Legal Protection and Certainty of Partner Doctors' Status in Partnership Relationships with Health Care Facilities: A Preventive Approach through Contract Models and Legal Risk Management - Arif Junaedi (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This article examines the legal protection and certainty of legal status for partner doctors who enter partnerships with health care facilities (fasyankes) in Indonesia, through a preventive approach based on the preparation of a partnership contract model and legal risk management. The issues studied include: (1) what form of legal protection and certainty of status of partner doctors in partnerships with health care facilities; (2) what is the ideal partnership contract model to avoid giving rise to a hidden employment relationship; and (3) how the implementation of legal risk management can minimize the potential for disputes between partner doctors and health care facilities. The method used is a juridical-normative approach with a statutory approach, as well as legal doctrine. The results of the study indicate that to ensure the certainty of status and protection of partner doctors, the partnership agreement must clearly state the doctor's clinical independence, be based on the sharing of business results risks, and integrate the health care facility's internal legal audit mechanism. Systematic legal risk management can prevent health care facilities from the potential recognition of hidden employment relationships and strengthen medical professional governance. The novelty of this research lies in the development of a preventive partnership contract model construction and the integration of legal risk management in the doctor-health care facility partnership relationship.